Motivating reluctant readers using the bibliotherapy technique : a case study in UiTM Melaka / Josephine Lourdunathan and Angeline Ranjethamoney Vijayarajoo - Lourdunathan, Josephine; Vijayarajoo, Angeline Ranjethamoney (Institute of Research, Development and Commercialization (IRDC), 2005)
Aliteracy has become a widespread concern in our country. Our young generation has become a group of reluctant readers due to the learning environment, among other factors. The learning environment focuses on academic achievement and most reading au/comes expected are confined only to academic success, neglecting the aesthetic appreciation oftextsfor its own sake. The researchers set out on a quest to find ways of motivating adolescent students in the ESL classroom, to begin /0 enjoy the pleasure of reading and through this, the other benefits of reading which they have deprived themselves of: knowledge. developing a personality, becoming a more interesting and wholesome individual, an asset to the community and workplace. The researchers believe that reluctant readers can be reached. given motivation and guidance. It is this thatformed the basis ofthis current research which aimed at investigating the potential role ofbibliotherapy, in encouraging unmotivated young adults to read extensively. Basically, bibliotherapy is a process/treatment which focuses on personalized and meaningful reading. A case study was conducted with five participants from the Pre-Teslgroup ofUiTM Melaka. Themethodology included uestionnaire. face-to-face interviews and log sheet. Thefindings ofthis research indicated the effectiveness and success ofbibliotherapy in motivating reluctant readers. All participants responded encouragingly to the sessions and have begun reading independently. The researchers recommend that bibliotherapy be used as an alternative method in teaching reading.